A Literature Review: Cross-Sector Collaboration Arrangements to Deliver Public Services and Goods - Qaedi Aqsa; Nugroho, Bernardus Yuliarto (Technium Social Sciences Journal, 2023)
Cross-sector collaboration is a growing topic in the discourse of new public governance. This topic is the importance of public managers collaborating with other actors outside the government, such as the private sector and non-profit organizations, in producing and delivering public goods and services. This journal uses a qualitative approach with a literature review method from books and journals that explains the concepts and approaches of cross-sector collaboration. The results of this study show a continuum of cross-sector collaboration approaches. Public managers can choose the approaches such as Government Provision, Contracting-out, Public Private Partnership (PPP), Network, and Independent Public Services Provider (IPSP). Each approach has its character, from the provision, financing, production process, relationship with society, and trust between actors.